Interventional cardiology : principles and practice - Barlis, Peter; Dangas, George D.; Di Mario, Carlo (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
This new volume offers a balanced and current presentation of the key topics that form the cornerstone of an Interventional Cardiology training program. Globally recognized editors and contributors draw on their years of experience to provide practical information emphasizing the basics of material selection and optimal angiographic setup for purposes of the interventional procedure. Comprehensive chapters address the different techniques of approaching complex coronary lesions such as chronic occlusions, bifurcations, and unprotected left main lesions.
Includes bibliographical references and index.
Keywords: Coronary heart disease -- Surgery; Coronary heart disease -- Surgery; Electronic books